Laparoscopy for the treatment of ovarian remnant syndrome in four dogs and two cats - Brückner, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2016)
Objective: To describe the clinical workup and laparoscopic treatment of ovarian remnant syndrome in dogs and cats. Material and methods: After confirming the diagnosis with some or all of the following tests – vaginoscopy with cytology, hormonal tests, and ultrasound – laparoscopic removal of the ovarian remnants was performed. A three-portal technique was used in the four dogs and a two-portal technique in the two cats. Results: All patients recovered well and were discharged the same day. No post-operative complications occurred in any patient. Conclusion and clinical relevance: Overall, in the hands of an experienced laparoscopic surgeon, laparoscopic removal of ovarian remnants appears to be a safe procedure in dogs and cats. In addition, laparoscopy offers the advantages of excellent visualization and a reduced morbidity for the patient. Careful case selection and complete pre-operative workup to rule out co-morbidities or underlying neoplasia are important. As with any laparoscopy the surgeon should always be prepared to convert to an open laparotomy if necessary.
Keywords: Ovarian remnant syndrome; laparoscopy; dog; cat